STUDY OF SCIENCE PHILOSOPHY: TAXATION IN INDONESIA REVIEW OF ISLAMIC SHARIA AND TAX LAW - B2092162002, BAYU JATI JATMIKA - (MAKSI UNTAN, 2019)
This study aims to understand the foundation of epistemology, ontology and axiology of the development of taxation systems and practices in Indonesia. Then to understand the administrative sanction paradigm in the form of fines, interest and increase from the perspective of Islamic Sharia and Tax Law and to know and understand the comparison of billing systems with forced letters in the perspective of Islamic Sharia and Tax Law. The method used is by observation, interview and literature study or literature review which is processed by means of data triangulation, theory, investigator and methodology.The analysis process begins by examining all the data obtained and then reduced through abstraction by making a core summary, categorization, finding meaning, and conceptualization, by giving interpretations to the data or sentences.Next, look for connections (connections) between various categories with descriptions and explanations that use theoretical thinking and reflection to find a synthesis and proposition.Â Keywords : Philosophy of Science, Ontology, Epistemology, Axiology, Administrative Sanctions, Tax Collection with Islamic Sharia Forced Mail, Tax Law